Paediatric mycosis fungoides – characteristics, management and outcomes with particular focus on the folliculotropic variant. (2nd March 2022) - Reiter, O.; Amitay‐Laish, I.; Oren‐Shabtai, M.; Feinmesser, M.; Ben‐Amitai, D.; Hodak, E.
Abstract: Background: The literature on paediatric mycosis fungoides (MF) and especially its folliculotropic variant (FMF) is sparse. Objectives: To describe the clinical manifestations, treatments, outcomes and long‐term course of paediatric MF, including FMF. Methods: A retrospective analysis was conducted of all consecutive MF patients diagnosed at ≤18 years attending two medical centres in 1995–2015. Results: The cohort included 71 patients, all but two of whom had early‐stage disease: hypopigmented (55%), folliculotropic (42%) and classical MF (39%), alone or in combination. The head and neck area were involved in 43% of patients with early‐stage FMF compared to 12% of the non‐FMF group ( P = 0.004). There was no difference in the involvement of other body areas between the groups. Pruritus, although mild, was more often recorded among patients with early‐stage FMF compared to non‐FMF (58% vs. 29%, respectively, P = 0.02). Complete response (CR) was achieved in 60 of the 69 patients with early‐stage MF (87%) after an average of 1.8 treatment modalities. NBUVB was the most administered treatment to non‐FMF patients with CR rates of 63% vs. 29% of FMF patients ( P = 0.04). Systemic/bath PUVA and UVA+NBUVB were the most administered treatments to FMF patients with CR rates of 60% vs. 81% for non‐FMF patients ( P = 0.17). During a mean follow‐up of 9.2 years (range 1–24), stage progression was observed in four (6%) of the patients with early‐stage disease, two of whom (all FMF) to advanced stage. Conclusions: Paediatric MF presents as an early‐stage disease with over‐representation of hypopigmented and FMF variants. NBUVB and UVA‐based therapies yield good response rates in non‐FMF and FMF patients, respectively. Disease course is indolent, and even on relatively long follow‐up, it has a very low progression rate from early to advanced‐stage disease, occurring in patients with FMF. We propose a treatment algorithm for paediatric MF.